Physicochemical properties, biological chemistry and mechanisms of action of caries-arresting diammine-silver(I) fluoride and silver(I)-fluoride solutions for clinical use: a critical review † - Hunwin, Kayleigh; Page, Georgina; Edgar, Mark; Botana, Adolfo; Armitage, Rachel; Bhogadia, Mohammed; Desai, Unmesh; Duffin, Steven; Duffin, Marcus; Chan, Wyman; Grootveld, Martin (Frontiers in Oral Health, 2024)
This paper serves as a Part II follow-up of our research investigations performed on the molecular structures of silver(I)-fluoride (SF) and diammine-silver(I) fluoride (SDF) complexes in solution-based commercial products for clinical application, their precise chemical compositions, and their nature in aqueous solution, the latter including rapid fluoride-exchange processes at the silver(I) ion centre monitored by 19F NMR analysis (Part I). Part I of this series also explores the mechanisms of action (MoA) of these complexes, and is therefore largely focused on their chemical reactions with constituents of human saliva, which has access to their sites of application. Such reactions were found to slowly promote the generation of potentially physiologically-active Ag/AgCl nanoparticles from primarily-generated discoloured silver(I) chloride (AgCl) precipitates, a process involving salivary electron-donors such as thiocyanate and L-cysteine. Since this research has shed new light on potential MoAs for these products, in this accompanying report (Part II), we have performed a critical review of scientific literature in order to rationalize our results in relation to current views on these mechanisms for SF and SDF products employed for the successful clinical arrest of dental caries. Following an Introduction to the subject matter ( Section 1), this paper comprises a generalized overview of silver coordination chemistry ( Section 2), which is followed by a section focused on the aqueous solution status and equilibria involved in SF chemistry ( Section 3), the latter including results acquired from an original simulation of the electronic absorption spectra of coloured SF complexes in aqueous solution (Section 3.1). Section 4 then investigates detailed rationales for the biologically-relevant ligand-exchange and redox chemistries, disposition and fates of SF, SDF and silver(I)-nitrate when employed for the treatment of dental caries, with emphasis placed on their therapeutic MoAs. This Section is supported by the provision of valuable information centralized on (1) relevant biomolecular chemistry involved in solution- and solid-state matrices ( Section 4.1); (2) SF and perhaps silver(I)-nitrate as more cost-effective alternatives to SDF therapies ( Section 4.2); and (3) the potential therapeutic benefits and effects offered by silver-based nanoparticles and their associated MoAs ( Section 4.3). Recommendations for future investigations in this area are proposed.